Anticonvulsants Following Craniotomy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
A randomized prospective clinical trial of carbamazepine or phenytoin for 6 or 24 months including a control no-treatment group is reported in 276 post-craniotomy patients at the Walton Hospital, Liverpool, England.